2021
DOI: 10.3389/fpsyg.2021.716106
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Human Support on the Effectiveness of Digital Mental Health Promotion Interventions for the General Population

Abstract: Mental wellbeing amongst the general population is languishing—exacerbated by the Coronavirus Disease 2019 (COVID-19) pandemic. Digital mental health promotion interventions, that improve mental health literacy and encourage adoption of evidence-informed practical strategies are essential. However, attrition and non-adherence are problematic in digital interventions. Human support is often applied as an antidote; yet, there is a paucity of randomized trials that compare different human support conditions among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Baseline completers were somewhat younger than noncompleters, suggesting that more support for participation may be needed for older adults. Baseline website engagement was higher for those of Hispanic ethnicity, whereas comfort in website use was greater for people preferring English, suggesting that website modification or human support may be important for non-English speakers [ 18 ]. In addition, less comfort in use was associated with having a prior overnight behavioral health stay, which could reflect disability or need for support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline completers were somewhat younger than noncompleters, suggesting that more support for participation may be needed for older adults. Baseline website engagement was higher for those of Hispanic ethnicity, whereas comfort in website use was greater for people preferring English, suggesting that website modification or human support may be important for non-English speakers [ 18 ]. In addition, less comfort in use was associated with having a prior overnight behavioral health stay, which could reflect disability or need for support.…”
Section: Discussionmentioning
confidence: 99%
“…Recruited participants included clients, partners, and providers of partnering agencies, and we did not track participant roles; however, baseline education data suggest the sample included some nonproviders. In future research, it may be important to include demographic or cultural differences in stigma of mental health that may affect website use to inform the tailoring of resources, and it may be important to evaluate the added value of human support to enhance website use and survey response, particularly for non-English speakers or older adults [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lift Project is a positively oriented 10-week education program that experientially engages participants in wellbeing-enhancing strategies from the disciplines of lifestyle medicine and positive psychology. The Lift Project was initially designed as a mental wellbeing program for generally healthy cohorts, and numerous studies, including randomized controlled trials, have reported positive outcomes among this target population ( Przybylko et al, 2021a ; Renfrew et al, 2021a ). However, stratified analyses have indicated that while the intervention adopts a positive orientation, participants with the lowest baseline MH metrics may benefit the most ( Morton et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, human support is increasingly used to augment WBIs ( Mohr et al, 2011 ). Guidance by coaches, therapists, or general practitioners may increase participants' accountability or motivation to complete the intervention and could also encourage them to adhere to the intervention through specific prompts, potentially increasing the effectiveness of such interventions( Renfrew et al, 2021 ; Mohr et al, 2011 ; Alkhaldi et al, 2016 ; Baumeister et al, 2014 ; Ryan et al, 2018 ; McCusker et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%